2014
DOI: 10.3109/00365521.2014.913189
|View full text |Cite
|
Sign up to set email alerts
|

Primary sclerosing cholangitis and the microbiota: current knowledge and perspectives on etiopathogenesis and emerging therapies

Abstract: Primary sclerosing cholangitis (PSC) is a chronic, fibroinflammatory, cholestatic liver disease of unknown etiopathogenesis. PSC generally progresses to liver cirrhosis, is a major risk factor for hepatobiliary and colonic neoplasia, and confers a median survival to death or liver transplantation of only 12 years. Although it is well recognized that approximately 75% of patients with PSC also have inflammatory bowel disease (IBD), the significance of this association remains elusive. Accumulating evidence now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 69 publications
1
81
0
1
Order By: Relevance
“…The epithelial lining cells (cholangiocytes) exhibit heterogeneities in their morphologies, phenotypes and gene expression along the biliary tree and function as a secretory/absorptive epithelium and other physiological roles [5][6][7][8]. Cholangiopathies are a diverse group of biliary disorders of distinct etiologies, and they include, for example, immune-mediated, drug-induced and infectious cholangiopathies [1,2,[9][10][11][12]. Among them, fibrosing cholangiopathies such as primary sclerosing cholangitis (PSC) and biliary atresia (BA) are characterized by cholangiocytic injuries and progressive fibrous obliteration of the biliary tree associated with nonspecific inflammatory cell infiltration [1,2,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epithelial lining cells (cholangiocytes) exhibit heterogeneities in their morphologies, phenotypes and gene expression along the biliary tree and function as a secretory/absorptive epithelium and other physiological roles [5][6][7][8]. Cholangiopathies are a diverse group of biliary disorders of distinct etiologies, and they include, for example, immune-mediated, drug-induced and infectious cholangiopathies [1,2,[9][10][11][12]. Among them, fibrosing cholangiopathies such as primary sclerosing cholangitis (PSC) and biliary atresia (BA) are characterized by cholangiocytic injuries and progressive fibrous obliteration of the biliary tree associated with nonspecific inflammatory cell infiltration [1,2,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Cholangiopathies are a diverse group of biliary disorders of distinct etiologies, and they include, for example, immune-mediated, drug-induced and infectious cholangiopathies [1,2,[9][10][11][12]. Among them, fibrosing cholangiopathies such as primary sclerosing cholangitis (PSC) and biliary atresia (BA) are characterized by cholangiocytic injuries and progressive fibrous obliteration of the biliary tree associated with nonspecific inflammatory cell infiltration [1,2,[9][10][11][12]. Whereas PSC and BA are considered complex disorders involving multiple etiopathogenetic factors, immune system-mediated assaults against the cholangiocytes are regarded a central feature [1,2,[9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…7 Data from basic and clinical studies have long supported the hypothesis that the intestinal microbiota may have a role in PSC pathogenesis. [8][9][10] Recently, studies using next-generation sequencing have reported a distinct fecal or mucosal microbiota composition in PSC-IBD patients. [11][12][13][14][15][16][17][18] There is a close interplay between gut flora and BA metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Composition of microbiota from intestinal biopsies of healthy controls and PSC patients demonstrated lower diversity and richness in PSC patients compared with non-inflammatory controls [161] . In line with the hypothesis that intestinal microbiome plays a role in pathogenesis of PSC [162] , interfering with the microbiome by antibiotic treatment may change the course of the liver disease. Various absorbable/systemic and non-absorbable antibiotics have been tested in PSC [163] and reported to induce biochemical improvement, with vancomycin being the most promising agent [164] .…”
Section: Bile Acids Receptors and Other (Nuclear Hormone) Receptorsmentioning
confidence: 78%